Improving The Ability To Read Kitab Kuning Through The Manhaji Method At Darun Nuhat Islamic Boarding School, Petiyin, Solokuro, Lamongan - Muhammad Arwani Rofi'i (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2024)
This study aims to evaluate the effectiveness of implementing the Manhaji Method in improving the ability to read Kitab Kuning (classical Islamic texts) at Darun Nuhat Islamic Boarding School, Petiyin-Solokuro, Lamongan. Kitab Kuning serves as the primary literature in pesantren (Islamic boarding schools) but often poses challenges for students due to limited understanding of Nahwu (Arabic grammar) and Sharaf (morphology). The Manhaji Method, systematically designed, offers a practical approach to studying Kitab Kuning through structured, tiered learning from basic to advanced levels. This research employs a qualitative approach with data collection techniques including observation, interviews, document studies, and reading ability tests. Data were collected from various sources such as pesantren leaders, teachers, and students through interviews and direct observation of the learning process. The study's results show that the implementation of the Manhaji Method significantly enhances students' understanding of Kitab Kuning, particularly in the aspects of Nahwu and Sharaf. Students demonstrated improved abilities in recognizing sentence structures, understanding word transformations, and applying grammatical rules effectively. This success is supported by competent teachers employing simple and systematic approaches, a well-structured, tiered curriculum from basic to advanced levels, and a conducive learning environment. The pesantren atmosphere, adequate facilities, and the collective enthusiasm of students created an optimal learning ecosystem. The efficiency of the Manhaji Method also increased students’ motivation through a structured and practical tiered learning process. This study recommends that the Manhaji Method be more widely adopted in other pesantren while considering local contexts. A broader application of this method is expected to support sustainable pesantren education, improve the quality of Kitab Kuning instruction, and strengthen the Islamic scholarly tradition in various educational institutions.Keywords: Manhaji Method; Kitab Kuning; Pesantren; Nahwu; Sharaf.